PUBLISHING INDUSTRY OF UZBEKISTAN: CURRENT STATUS AND DEVELOPMENT PROSPECTS (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2025)
Uzbekistan publishing house industry last in years noticeable to changes is occurring . Print and electronic publications development , state by support​ programs and global competition this to the field impact indicator main from factors This is​ in research Uzbekistan​ publishing house market current status analysis published​​ of the field main problems , including authorship​ rights , economic difficulties and reading culture changes seeing The article is published . main purpose Uzbekistan​ publishing house industry today's condition scientific in terms of study and in the future his/her stable development provision for necessary strategies is to determine .